2014
DOI: 10.1007/s10561-014-9486-1
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to preserve human osteochondral allografts

Abstract: Osteochondral defects may progress to osteoarthritis. Many attempts have been developed to overcome this issue, including osteochondral autografts and allografts. The goal of this study was to develop a new protocol for storage of human osteochondral allografts. Osteochondral plugs were randomly allocated in the following groups: control, immediate freezing up to -70 °C, cooling at 4 °C, and storage at 37 °C. Samples from the cooling at 4 °C and storage at 37 °C groups were stored in tubes containing medium pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…One particular work by Mueller-Rath et al ( 2007) stands out from the literature that describes a cultivation of autologous chondrocytes in a defect created in a OCT graft and then implanted in subcutaneous pockets of nude mice. The remaining five papers had cultivation times more homogeneous of 2, 3, and 4 weeks (Brecelj et al, 2007;Lyman et al, 2012;Gavénis et al, 2010;Secretan et al, 2010;de Sousa et al, 2015). In particular, the study Although all papers describe careful washing steps of the samples to remove as much as possible bone marrow from the subchondral bone the experimental set ups, on the other hand, vary greatly.…”
Section: Human-derived Octmentioning
confidence: 99%
See 1 more Smart Citation
“…One particular work by Mueller-Rath et al ( 2007) stands out from the literature that describes a cultivation of autologous chondrocytes in a defect created in a OCT graft and then implanted in subcutaneous pockets of nude mice. The remaining five papers had cultivation times more homogeneous of 2, 3, and 4 weeks (Brecelj et al, 2007;Lyman et al, 2012;Gavénis et al, 2010;Secretan et al, 2010;de Sousa et al, 2015). In particular, the study Although all papers describe careful washing steps of the samples to remove as much as possible bone marrow from the subchondral bone the experimental set ups, on the other hand, vary greatly.…”
Section: Human-derived Octmentioning
confidence: 99%
“…reported byde Sousa et al (2015) on a large number of patients (22) and a very large number of specimens (220 OCTs) analyzed the best culture conditions and compared specimen cultivated at 4 or 37°C for 1, 3, and 14 days. Major findings showed an increase in cell death at 14 days in comparison with shorter experimental times, and when plugs were cultured at 37°C in comparison with 4°C.…”
mentioning
confidence: 99%
“…11 Preservation of human osteochondral allografts has previously been studied for the treatment of knee lesions. 16,17 Regarding the shoulder, few studies have evaluated the use of osteochondral allografts for treating humeral head articular cartilage lesions. 7 The few existing reports have mainly described the use of frozen allografts, 7,18,19 whereas studies involving the use of fresh allografts are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In a preliminary study, performed with surgical disposal material, our group showed that refrigeration at 4°C offers better preservation capacity of osteochondral fragments than at 37°C for up to 14 days. 18 For this reason, in the current study with young CD tissues, we kept the option of cooling the fragments to 4°C. Our results confirm previous findings that the temperature of 4°C is adequate for allograft preservation.…”
Section: Discussionmentioning
confidence: 99%